BdACT2a encodes an agmatine coumaroyl transferase required for pathogen defence in Brachypodium distachyon. (December 2018) - Carere, Jason; Powell, Jonathan; Fitzgerald, Timothy; Kazan, Kemal; Gardiner, Donald M.
Abstract: Plants have a variety of enzymes which help defend from pathogen attack by producing antimicrobial compounds. One of these enzymes, agmatine coumaroyl transferase (ACT) is responsible for producing hydroxycinnamic acid amides (HCAAs). In this study, we identified a tightly clustered group of ACT genes in Brachypodium distachyon responsive to Fusarium infection and functionally characterised one of these genes designated as BdACT2a . It was found that when expression of BdACT2a is disrupted, Brachypodium becomes more susceptible to Fusarium pseudograminearum . BdACT2a has broad substrate specificity and feruloylagmatine is produced in significantly lower quantities in the Bdact2a line compared to wild-type Brachypodium . Feruloylagmatine appears to inhibit spore germination but not mycelium growth of Fusarium. This report demonstrates that BdACT2a is important for plant defence and ACTs may have a conserved defensive role in plants. Highlights: Brachypodium contains a clustered group of ACT genes responsive to Fusarium. Disruption of BdACT2a leads to increased susceptibility to infection by Fusarium . BdACT2a disruption leads to lower amounts of Feruloylagmatine in planta . Feruloylagmatine inhibits spore germination but not mycelium growth. BdACT2a has broad substrate specificity.